2014
DOI: 10.1016/j.jacc.2013.04.105
|View full text |Cite
|
Sign up to set email alerts
|

Early High-Dose Rosuvastatin for Contrast-Induced Nephropathy Prevention in Acute Coronary Syndrome

Abstract: High-dose rosuvastatin given on admission to statin-naïve patients with ACS who are scheduled for an early invasive procedure can prevent CI-AKI and improve short-term clinical outcome. (Statin Contrast Induced Nephropathy Prevention [PRATO-ACS]; NCT01185938).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(82 citation statements)
references
References 39 publications
1
76
1
4
Order By: Relevance
“…Leoncini et al [171] treated 252 patients with acute coronary syndrome, who were scheduled for an early invasive procedure and were at high risk for contrast-induced AKI, with high doses of rosuvastatin, that is, 40 mg on admission, followed by 20 mg/day. The incidence of AKI was significantly lower in the statin group than in controls (6.7% versus 15.1%, P = 0.003).…”
Section: Prevention Of Akimentioning
confidence: 99%
“…Leoncini et al [171] treated 252 patients with acute coronary syndrome, who were scheduled for an early invasive procedure and were at high risk for contrast-induced AKI, with high doses of rosuvastatin, that is, 40 mg on admission, followed by 20 mg/day. The incidence of AKI was significantly lower in the statin group than in controls (6.7% versus 15.1%, P = 0.003).…”
Section: Prevention Of Akimentioning
confidence: 99%
“…Many studies have shown the efficacy of pretreatment with statins in decreasing the risk of developing CI-AKI in patients undergoing coronary interventions [26, 27]. In a meta-analysis of 15 controlled trials, Liang et al [28] demonstrated the efficacy of pretreatment with rosuvastatin in reducing the incidence of CI-AKI in patients undergoing coronary interventions ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the pharmacological effects of active constituents are in positive correlation with their dose within certain limits. [41][42][43] Accordingly, the score of PF1 and PF2 could reflect the quality of Dianbaizhu in some degrees. The higher factor score was, the better quality was (Fig.…”
Section: Methods Validationmentioning
confidence: 99%